2022
DOI: 10.1111/tmi.13720
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with unsuccessful tuberculosis treatment outcomes in Hunan Province, China

Abstract: Objectives: Globally, China has the third highest number of tuberculosis (TB) cases despite high rates (85.6%) of effective treatment coverage. Identifying risk factors associated with unsuccessful treatment outcomes is an important component of maximising the efficacy of TB control programmes.Methods: Retrospective cohort study to evaluate the outcomes of 306,860 drugsusceptible TB patients who underwent treatment in Hunan Province, China between 2013 and 2018. Univariable and multivariable logistic regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 37 publications
1
4
0
1
Order By: Relevance
“…Several studies have shown that many factors such as HIV status, age and site of tuberculosis are associated with TB treatment outcome [15,16,23,25,26,28]. In the present study, the associated factor is age alone and this is similar to the findings from Madda Walabu University Goba Referral Hospital [16], Malaysia [26], Nigeria [23], Kilifi country of Kenya [29], Uganda PLOS ONE [25] and Hunan state of China [30]. The finding that TB treatment success rate was lower in patients older than 44 years is in agreement with study conducted on TB patients of Gambella regional state of Ethiopia [31].…”
Section: Discussionsupporting
confidence: 89%
“…Several studies have shown that many factors such as HIV status, age and site of tuberculosis are associated with TB treatment outcome [15,16,23,25,26,28]. In the present study, the associated factor is age alone and this is similar to the findings from Madda Walabu University Goba Referral Hospital [16], Malaysia [26], Nigeria [23], Kilifi country of Kenya [29], Uganda PLOS ONE [25] and Hunan state of China [30]. The finding that TB treatment success rate was lower in patients older than 44 years is in agreement with study conducted on TB patients of Gambella regional state of Ethiopia [31].…”
Section: Discussionsupporting
confidence: 89%
“…Another study conducted in Nigeria [75] showed no significant difference in treatment failure between the smear positive and smear negative test results. The findings of this study can be attributed to presence of atypical mycobacterium bacilli that are not sensitive to the first line treatment of TB treatment 2(RHZE) 4(RH) [76] Second line treatment starts in already advanced bacillary load. Futhermore it has been established that patients who initiated treatment with high bacillary load at the initial phase of treatment are more likely to have treatment failure than those with lower bacillary load.…”
Section: Discussionmentioning
confidence: 78%
“…Futhermore it has been established that patients who initiated treatment with high bacillary load at the initial phase of treatment are more likely to have treatment failure than those with lower bacillary load. [76] This findings underscores the need to screen patients for atypical TB bacilli prior to initiation of treatment and minimization of delay between development of symptomatic TB and diagnosis.…”
Section: Discussionmentioning
confidence: 84%
“…The comparison indicates that the burden of post-TB in Inner Mongolia was heavy. China has increased its efforts to screen for TB [ 52 ], but the focus is still on prevention and treatment while neglecting the follow-up of cured patients with TB. Although TB control focused on cutting off the transmission and curing patients, the completion of TB treatment might be the beginning of the chronic respiratory disease [ 53 ].…”
Section: Discussionmentioning
confidence: 99%